Rectify - Season 1 Episode 1-6 - Gordon, Keith; Gierhart, Bill; Kassell, Nicole; Sommers, Paul M.; Young, Aden; Spencer, Abigail; Clemens, Adelaide (Just Entertainment, 2015)
When Daniel Holden is released after 19 years of complete isolation on death row, he returns as an outsider to his family, to his community, and to the times. Somehow, he survived the mental and emotional strain of his imprisonment, but now the walls have suddenly come crumbling down and Daniel is set free in a world he no longer understands. He's an outsider, lost in a once familiar world, struggling to navigate his newfound freedom. [www.amazon.com]